Conflict & diplomacy from the great war to the cold war - Shepardson, Donald E. (Studies in modern European history, 1999)
"Conflict and Diplomacy from the Great War to the Cold War begins with the weakening of the old European order in World War I the challenge of communism and fascism to the established international system. The author examines the origins of World War II in Asia and Europe and the advent of global war following the German attack on the Soviet Union, as well as Japanese aggression in the Pacific. The middle chapters cover the period of Axis triumph to the turning points of El Alamein and Stalingrad. The prospect of Allied victory helped to bring the disintegration of the grand alliance and a return to the Soviet-Western rivalry, which existed prior to World War II. The final part of the book deals with the defeat of Japan and the controversy surrounding the atomic bomb."--BOOK JACKET.